The development of Virtual Javanese Gamelan to improve Gamelan learning achievement - Mohammad Safari; Dennis Ossy January (Prodi PGMI IAIN Salatiga, 2018)
This study aims to develop innovative, effective and practical learning media to improve learning achievement of students in memorizing and recognizing the basic instruments of gamelan. The background of this study is that there are still many elementary school (SD) and Islamic elementary school (MI) students who do not know the basic instruments of gamelan, which hinder the achievement of Javanese language competencies. This method of developing learning media uses research and development method steps. Dissemination is carried out at the Central Java Center of Education Information and Communication Technology Development (BPTIKP) for the implementation toward more targeted users. The results of the study show that they have succeeded in developing the Virtual Virtual Javanese Gamelan in which the students can use to play while learning. The learning results show a significant increase in learning achievement, in the initial conditions without using Virtual Javanese Gamelan, from 18 students, only 5 students (27.8%) have completed the learning with an average score of 66. While the learning results obtained after using the Mutimedia Virtual Javanese Gamelan, the completion reaches 18 students (100%) with an average score of 90. So it can be concluded that Virtual Javanese Gamelan multimedia can improve the learning achievement of the second graders at MI Miftahul Huda 01.